Putin's "re-election": An undemocratic, authoritarian plebiscite - Sabine Fischer (Stiftung Wissenschaft und Politik (SWP), 2024)
No Russian election since Soviet times has been manipulated to the extent we are seeing in the 2024 'presidential election'. The political context is dictatorial, the regime's power grab comprehensive. The media are subject to wartime censorship, and there is not even a pretence of political competition. The death of Alexei Navalny has only heightened the atmosphere of fear. Yet although the vote is an authoritarian plebiscite, a rubber stamp, signs of popular criticism of the regime and the war should not be overlooked. Germany and Europe should unequivocally state that this election is undemocratic and illegitimate. But even more importantly, contacts with critics of the war inside Russia must be maintained.
Keywords: 320; Russian election; democratic opposition; Vladimir Putin; Alexei Navalny; Margarita Simonyan; United Russia; war in Ukraine